Socioeconomia solidária: tecendo novas relações sociais no Conjunto Palmeiras - Rodrigues, Maria Fernanda de Sousa (2003)
This dissertation examines the widespread social relations in recent years under the sign of the economic and social solidarity , from a new profile for the organization of social movements . These new arrangements arise as an alternative generated within capitalism in Brazil and worldwide , are organizations of workers and unemployed in large cities that through globalization " in reverse" , try to reverse the logic of production and consumption in neoliberal capitalism and global and locally reinvent everyday from daring, printing new paradigms in addressing social issues . The Conjunto Palmeira , located on the outskirts of Fortaleza , proposes , since 1998 , an alternative that enables improvement in quality of life of its residents . This neighborhood is examined in the current research work through an interpretive approach , which seeks to understand the forms of sociability that reveal or construct these social actors in everyday life , and as a field of research endeavors of Banco Palmas , a bank " created " by the Association of Residents of Conjunto Palmeira .